RÉPUBLIQUE DU BURUNDI (African Disability Rights Yearbook, 2021)
According to the 2008 census, Burundi has a population of 8 053.574 inhabitants. However, according to a projection by the Institut de Statistiques et D’Etudes Economiques du Burundi (ISTEEBU) the population of the country in 2019 is estimated to be at 12.044.164 inhabitants. The percentage of people with disabilities is unknown. The Republic of Burundi signed the United Nations Convention on the Rights of Persons with Disabilities (CRPD) on 26 April 2007 and ratified it on 26 March 2014. The Optional Protocol to the Convention on the Rights of Persons with Disabilities was signed and ratified in the same period. The Constitution of Burundi refers to disability. Article 22 reaffirms the protection and equality of everyone before the law and that no one may be subject to discrimination including among others on the ground of disability. The Republic of Burundi has numerous pieces of legislation that directly frame disability. The key ones are Law 1/03 of 10 January 2018 on the protection and promotion of the rights of people with disabilities in Burundi. Similarly, Law 1/20 of 3 June 2014 amending Law 1/22 of 18 September 2009 on the Electoral Code addresses disability. In the same vein, decree 100/216 of 4 August 2011 relating to the structure, functioning and missions of the Ministry of national solidarity frames disability. The policies that directly address persons with disabilities are: the National policy of people with disabilities and its action plan; the National policy in favour of orphans and other vulnerable children. Other than ordinary courts or tribunals, Burundi has an official body that specifically addresses the violation of the rights of persons with disabilities. It is the National Committee of the Rights of People with Disabilities/Comité National des Droits des Personnes Handicapées (CNDHP)] provided for by article 38 of Law 1/03 du 10 January 2018 on the protection and promotion of the Rights of persons with disabilities in Burundi. The Republic of Burundi has an Independent National Human Rights Commission [Commission Nationale Indépendante des Droits de l'Homme (CNIDH)] setup by Law 1/04 of 5 January 2011. There are numerous organisations that represent and advocate for the rights and welfare of persons with disabilities in Burundi. These include among others, the Network of Centre for Persons with Disabilities in Burundi [Réseau des Centres pour Personnes Handicapées au Burundi (RCPHB)], the Network of Associations of Persons with Disabilities in Burundi [le Réseau des Associations des Personnes Handicapées au Burundi (RAPHB)], the Union of Persons with Disabilities of Burundi [l’Union des Personnes Handicapées du Burundi (UPHB)] and the Federation of Associations of Persons with Disabilities of Burundi [la Fédération des Associations des Personnes Handicapées du Burundi (FAPHB)]. In Burundi, the Ministry of National Solidarity, of the rights of the Human Person and Gender deals with disability. Its Department of Social Integration is in charge of ensuring the protection of vulnerable peoples including persons with disabilities. Persons with disabilities enjoy little or no access to work, for many of them are unemployed. In addition, there is no specific process aimed at facilitating their employment in the public sphere as well as in private settings. As far as access is concerned, persons with disabilities have difficulties to access public buildings, public transport, education, vocational training, health care and other basic needs. The Burundian Government shall initiate measures to enhance the political participation of persons with disabilities in state affairs. In addition, there is a need to introduce the teaching of the rights of persons with disabilities at schools and universities across the country.
Keywords: Burundi; people with disabilities; protection and equality; disability legislation; access